Plate prebending using a three-dimensional–printed model affords effective anatomical reduction in clavicular shaft fractures - Hyungsuk Kim; Younsung Jung; Hyun Seok Song (Clinics in Shoulder and Elbow, 2023)
Background A precontoured plate rarely fits properly within the patient’s clavicle and must be bent intraoperatively. This study aimed to determine whether anatomical reduction could be achieved using a plate bent before surgery. Methods This study included 87 consecutive patients with displaced mid-shaft clavicle fractures who underwent plate fixation and were followed-up for a minimum of 1 year. After exclusions, 39 consecutive patients underwent fixation with a precontoured plate bent intraoperatively (intraoperative bending group), and 28 underwent fixation with the plate bent preoperatively (preoperative bending group). Using free software and a three-dimensional (3D) printer, ipsilateral clavicle 3D-printed models were constructed. Using plain radiographs, the distance between the edge of the lateral inferior cortex and the medial inferior cortex was measured. The angle between the line connecting the inferior cortex edge and the line passing through the flat portion of the superior cortex of the distal clavicle was measured. Results Mean length differences between the ipsilateral and contralateral clavicle were smaller on both anteroposterior (AP; P=0.032) and axial images (P=0.029) in the preoperative bending group. The mean angular differences on both AP (P=0.045) and axial images (P=0.008) were smaller in the preoperative bending group. No significant differences were observed between the two groups in functional scores at the last follow-up. Conclusions Smaller differences in length and angle between the ipsilateral and contralateral clavicle, indicative of reduction, were observed in the preoperative bending group. Using the prebending technique with low expense, the operation was performed more effectively as reflected by a shorter operation time. Level of evidenceIII.